Skew constacyclic codes over finite commutative semi-simple rings - Hai Q. Dinh (2019)
© 2019 Korean Mathematical Society. This paper investigates skew Θ-λ-constacyclic codes over R = F0 ⊕ F1 ⊕ · ⊕ Fk−1, where Fi’s are finite fields. The structures of skew λ-constacyclic codes over finite commutative semi-simple rings and their duals are provided. Moreover, skew λ-constacyclic codes of arbitrary length are studied under a new definition. We also show that a skew cyclic code of arbitrary length over finite commutative semi-simple rings is equivalent to either a cyclic code over R or a quasi-cyclic code over R.